2019
DOI: 10.1371/journal.pntd.0007197
|View full text |Cite
|
Sign up to set email alerts
|

Renal and vascular effects of kallikrein inhibition in a model of Lonomia obliqua venom-induced acute kidney injury

Abstract: Background Lonomia obliqua venom is nephrotoxic and acute kidney injury (AKI) is the main cause of death among envenomed victims. Mechanism underlying L . obliqua -induced AKI involves renal hypoperfusion, inflammation, tubular necrosis and loss of glomerular filtration and tubular reabsorption capacities. In the present study, we aimed to investigate the contribution of kallikrein to the hemodynamic instability, inflammation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 61 publications
1
21
1
Order By: Relevance
“…Additionally, it was observed that L. obliqua venom induces the production of several cytokines, increased the expression of matrix metalloproteinases (MMPs) and increased the levels of nitric oxide (NO). As a consequence, these alterations resulted in tubular lesions and hereby the role of the activation of kininogen-kallikrein-BK-B1R/B2R in L. obliqua envenomation was shown [50]. Moreover, this work pointed out that cytokines and coagulation factors are produced in the plasma during the envenomation.…”
Section: Acute Kidney Injurymentioning
confidence: 64%
See 4 more Smart Citations
“…Additionally, it was observed that L. obliqua venom induces the production of several cytokines, increased the expression of matrix metalloproteinases (MMPs) and increased the levels of nitric oxide (NO). As a consequence, these alterations resulted in tubular lesions and hereby the role of the activation of kininogen-kallikrein-BK-B1R/B2R in L. obliqua envenomation was shown [50]. Moreover, this work pointed out that cytokines and coagulation factors are produced in the plasma during the envenomation.…”
Section: Acute Kidney Injurymentioning
confidence: 64%
“…Firstly, they discovered that bradykinin, released from LMWK (directly) and HMWK (indirectly), as described previously in the section Contact Dermatitis with Edema and Erythema, contributes to kidney injury mainly by the activation of its two receptors, B1R and B2R [50]. Both receptors belong to the G-protein-coupled receptor group.…”
Section: Acute Kidney Injurymentioning
confidence: 85%
See 3 more Smart Citations